2019
DOI: 10.1039/c8np00061a
|View full text |Cite
|
Sign up to set email alerts
|

Marine chemical ecology in benthic environments

Abstract: This review highlights the 2013–2015 marine chemical ecology literature for benthic bacteria and cyanobacteria, macroalgae, sponges, cnidarians, molluscs, other benthic invertebrates, and fish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 80 publications
2
56
0
Order By: Relevance
“…Entotheonella serta” is a source of natural products in chemically distinct sponges T. swinhoei WA and WB (white interior) . It is likely that many natural products of “Entotheonella” are involved in host defense, which is a role often suspected or shown for toxic compounds of sessile invertebrates …”
Section: Introductionmentioning
confidence: 99%
“…Entotheonella serta” is a source of natural products in chemically distinct sponges T. swinhoei WA and WB (white interior) . It is likely that many natural products of “Entotheonella” are involved in host defense, which is a role often suspected or shown for toxic compounds of sessile invertebrates …”
Section: Introductionmentioning
confidence: 99%
“…Benthic species, particularly corals, are highly competitive [60] and have been classified based on their aggressiveness [61][62][63][64]. Corals compete either by direct physical contact or via the production and secretion of secondary metabolites that can weaken or kill neighboring organisms [65][66][67][68][69][70]. These metabolites are produced by the coral host itself or by their associated microorganisms, some of which are known to synthetize toxic compounds [67,71].…”
Section: The Composition Of Benthic Species Assemblages Influences Thmentioning
confidence: 99%
“…The most recent research has shown the inhibition of marine biofouling by different types of bacteria, cyanobacteria, and marine fungi. Recent experiments have shown the antifouling properties of some organic compounds [72,73], marine larvae of epibiotic bacteria [74][75][76], and various natural chemical compounds [77]. Dobretsov et al [78] studied the microbial interference as a mechanism to control marine biofilms, focusing on the mechanisms of altering the biofilm by bacteria, algae, and various larvae.…”
Section: Biological Treatments Antifoulingmentioning
confidence: 99%